The Influence of Brand Ambassador, User Interface and Free Shipping Program on Purchasing Decisions through Tokopedia E-commerce with Brand Trust as an Intervening Variable - Anindya, Annisa; Arslan, Rijal; Mendrofa, Kristiurman Jaya (IJBLE Scientific Publications Community Inc., 2025)
This study aims to evaluate the influence of Brand Ambassador, User Interface, and Free Shipping Programme on E-Commerce Tokopedia, with Brand Trust acting as an intervening variable. This study employs quantitative approaches and purposive sampling procedures with a sample of 100 respondents. Employing path analysis with Smart PLS version 3 for data analysis. The study's findings demonstrate that brand ambassadors have a favourable and substantial effect on brand trust; nevertheless, their influence on purchasing decisions through Tokopedia is negligible. The user interface has a positive and substantial impact on brand trust and purchasing decisions. The Free Shipping Programme affects brand confidence and purchasing decisions. Brand trust successfully mediates the impact of Brand Ambassador, User Interface, and Free Shipping Programme on purchasing decisions.